1995
DOI: 10.1002/ajmg.1320600616
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of close linkage between the synaptic vesicular monoamine transporter locus and schizophrenia spectrum disorders

Abstract: The principal brain synaptic vesicular monoamine transporter (VMAT2) is responsible for the reuptake of serotonin, dopamine, norepinephrine, epinephrine, and histamine from the cytoplasm into synaptic vesicles, thus contributing to determination of the size of releasable neurotransmitter vesicular pools. Potential involvement of VMAT2 gene variants in the etiology of schizophrenia and related disorders was tested using polymorphic VMAT2 gene markers in 156 subjects from 16 multiplex pedigrees with schizophreni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 11 publications
0
17
0
2
Order By: Relevance
“…DAT1 gene variants do not appear to provide widespread contributions to the etiology of schizophrenia spectrum disorders, according to linkage studies. 18,25 Most of the previous studies on the VNTR polymorphism of the DAT1 gene showed no positive evidence of allelic association between DAT1 alleles and schizophrenia, however, one of the studies showed that the DAT1 genotype distribution in schizophrenic patients did display a statistically significant departure from the genotype distribution found in controls. 26 There was no significant difference between controls and schizophrenic patients in the present study in both allelic and genotypic distributions of the novel polymorphism of the DAT1 gene, nor in the haplotype analysis.…”
Section: Discussionmentioning
confidence: 94%
“…DAT1 gene variants do not appear to provide widespread contributions to the etiology of schizophrenia spectrum disorders, according to linkage studies. 18,25 Most of the previous studies on the VNTR polymorphism of the DAT1 gene showed no positive evidence of allelic association between DAT1 alleles and schizophrenia, however, one of the studies showed that the DAT1 genotype distribution in schizophrenic patients did display a statistically significant departure from the genotype distribution found in controls. 26 There was no significant difference between controls and schizophrenic patients in the present study in both allelic and genotypic distributions of the novel polymorphism of the DAT1 gene, nor in the haplotype analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Nine-repeat allele carriers have also be found to be less likely to be tobacco smokers (Lerman et al 1999;Sabol et al 1999). On the other hand, this VNTR polymorphism is not associated with polysubstance abuse (Persico et al 1993), cocaine dependence (Gelernter et al 1994), delusional disorder (Persico and Catalano 1998), schizophrenia (Byerley et al 1993;Persico et al 1995), Tourette's syndrome (Gelernter et al 1995;Vandenbergh et al 2000), or alcoholism itself (Sander et al 1997;Vandenbergh et al 2000).…”
mentioning
confidence: 99%
“…Persico et al 16 examined the TaqI RFLP polymorphism of the SVMT gene 13 for linkage analysis in 16 multiplex pedigrees with schizophrenia spectrum disorders. They obtained results excluding close linkage between the SVMT gene and schizophrenia spectrum disorders in their pedigrees.…”
mentioning
confidence: 99%